2018
DOI: 10.1080/14767058.2018.1427060
|View full text |Cite|
|
Sign up to set email alerts
|

Patency of uterine wall in pregnancies following assisted and spontaneous conception with antecedent laparoscopic and abdominal myomectomies – a difficult case and systematic review

Abstract: A case of uterine rupture at 24 weeks in a pregnancy succeeding myomectomy and triple embryo transfer is described and literature is reviewed systematically to evaluate the importance of uterine rupture in pregnancies after myomectomy in general and some important sub-populations. Systematic search identified 179 papers and following a strategical selection process 45 studies were analyzed in detail, including 6 cohort and 19 observational studies, 3 case series and 17 case reports. Comparison of risk of uteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 57 publications
0
24
3
Order By: Relevance
“…In the previous studies, although uterine rupture occurred at various gestation, it occurred more often before the onset of labor, with a high rate of fetal loss. 5,18 In this study, the incidence of uterine rupture in women with a history of myomectomy was 0.22%, which is less than the reported incidence of uterine rupture (0.4-0.7%) in a trial of labor after cesarean section. 19,20 Possible reasons can be a missing diagnosis when uterine rupture or dehiscence was combined with placental abruption or antepartum/postpartum bleeding in the middle of pregnancy.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In the previous studies, although uterine rupture occurred at various gestation, it occurred more often before the onset of labor, with a high rate of fetal loss. 5,18 In this study, the incidence of uterine rupture in women with a history of myomectomy was 0.22%, which is less than the reported incidence of uterine rupture (0.4-0.7%) in a trial of labor after cesarean section. 19,20 Possible reasons can be a missing diagnosis when uterine rupture or dehiscence was combined with placental abruption or antepartum/postpartum bleeding in the middle of pregnancy.…”
Section: Discussioncontrasting
confidence: 56%
“…The incidences of preterm birth and uterine rupture after myomectomy have been variously reported to range from 3.1% to 35% 171717171717 and from 0.2 to 3.7%, respectively. 17,18 The previous systematic review including all cohort studies with at least ve cases demonstrated that the overall incidence of uterine rupture after myomectomy was 0.93% (0.45-1.92%) (n = 7/756); speci cally, it was 0.47% (0.13-1.70%) (n = 2/426) in women undergoing a trial of labor after myomectomy, and 1.52% (0.65-3.51%) (n = 5/330) in women before the onset of labor. 5 However, the number of pregnancies and viable deliveries after prior myomectomy were 2,367 and 1,284, respectively, from a total of 23 studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, although uterine rupture occurred at various gestation, it occurred more often before the onset of labor, with a high rate of fetal loss. 5,19 In this study, the incidence of uterine rupture in women with a history of myomectomy was 0.22%, which is less than the reported incidence of uterine rupture (0.4-0.7%) in a trial of labor after cesarean section. 20,21 Possible reasons can be a missing diagnosis when uterine rupture or dehiscence was combined with placental abruption or antepartum/postpartum bleeding in the middle of pregnancy.…”
Section: Discussioncontrasting
confidence: 56%
“…The incidences of preterm birth and uterine rupture after myomectomy have been variously reported to range from 3.1% to 35% and from 0.2 to 3.7%, respectively. 18,19 The previous systematic review including all cohort studies with at least ve cases demonstrated that the overall incidence of uterine rupture after myomectomy was 0.93% (0.45-1.92%) (n = 7/756); speci cally, it was 0.47% (0.13-1.70%) (n = 2/426) in women undergoing a trial of labor after myomectomy, and 1.52% (0.65-3.51%) (n = 5/330) in women before the onset of labor. 5 However, the number of pregnancies and viable deliveries after prior myomectomy were 2,367 and 1,284, respectively, from a total of 23 studies.…”
Section: Discussionmentioning
confidence: 99%
“…The incidences of preterm birth and uterine rupture after myomectomy have been variously reported to range from 3.1% to 35% 18 and from 0.2 to 3.7%, respectively. 18,19 The previous systematic review including all cohort studies with at least ve cases demonstrated that the overall incidence of uterine rupture after myomectomy was 0.93% (0.45-1.92%) (n = 7/756); speci cally, it was 0.47% (0.13-1.70%) (n = 2/426) in women undergoing a trial of labor after myomectomy, and 1.52% (0.65-3.51%) (n = 5/330) in women before the onset of labor. 10 However, the number of pregnancies and viable deliveries after prior myomectomy were 2,367 and 1,284, respectively, from a total of 23 studies.…”
Section: Discussionmentioning
confidence: 99%